Evaluating the Impact of Human Amnion Epithelial Cells on Angiogenesis - Dandan Zhu; Ruth Muljadi; Siow Teng Chan; Patricia Vosdoganes; Camden Lo; Joanne C. Mockler; Euan M. Wallace; Rebecca Lim (Hindawi Limited, 2016)
The effects of human amnion epithelial cells (hAECs) on angiogenesis remain controversial. It is yet unknown if the presence of inflammation and/or gestational age of hAEC donors have an impact on angiogenesis. In this study, we examined the differences between term and preterm hAECs on angiogenesis in vitro and in vivo. Conditioned media from term hAECs induced the formation of longer huVEC tubules on Matrigel. Both term and preterm hAECs expressed VEGFA, PDGFB, ANGPT1, and FOXC1, which significantly increased after TNFα and IFNγ stimulation. In the presence of TNFα and IFNγ, coculture with term hAECs reduced gene transcription of Tie-2 and Foxc1 in huVECs, while coculture with preterm hAECs increased gene transcription of PDGFRα and PDGFRβ and reduced gene transcription of FOXC1 in huVECs. In vivo assessment of angiogenesis using vWF immunostaining revealed that hAEC treatment decreased angiogenesis in a bleomycin model of lung fibrosis but increased angiogenesis in a neonatal model of hyperoxia-induced lung injury. In summary, our findings suggested that the impact of hAECs on angiogenesis may be influenced by the presence of inflammation and underlying pathology.